ANTESEDEN DAN KONSEKUENSI PEMANFAATAN TEKNOLOGI SISTEM INFORMASI AKUNTANSI PADA PERUSAHAAN DI KOTA BALIKPAPAN (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2014)
The main objective of this study is to examine the factors that are antecedents to use information technology, as well as the consequences of the use of information technology in accounting employees in Singapore, with reference to previous studies that have been conducted in several service organizations. Based on the research results, the use of accounting information technology employees in the accounting department at the company resulted in the conclusion that the use of information technology is influenced by factors Affect and long-term consequences but is not influenced by social factors, complexity, compliance tasks, and facilitating conditions. And of the results of the regression utilization of information technology does not affect the performance.